IRONY IN ANIMAL FARM BY GEORGE ORWELL - Shidqi Fauzia Ruliff; Sofa Nur Alfiah; Fadly Yusuf Thoziry; Nurholis (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
This study discusses the use of irony in George Orwell’s Animal Farm, illustrating how Orwell engages various forms of irony to critique politics and human nature. Through three types of irony, specifically verbal, dramatic, and situational irony. The novel exposes the hypocrisy and corruption of the pigs, particularly in their manipulation of language and principles. Verbal irony that shows the exaggerated praises that showered the pigs. Also, the transformation of the pigs into a tyrant is shown as a powerful example of situational irony, while the animal’s blind acceptance of the pigs leadership deepens the dramatic irony, as the reader understands the truth behind the facade. This study also explores how the novel uses irony to critique the cynical nature of power and oppression. The research method of this study is a descriptive qualitative method. This data was obtained from the novel as the main source and research journals as supporting theories for this research.